Mathematical Literacy in School Mathematics Learning: A Literature Review of Challenges and Instructional Strategies - Rizki Apriva Hidayana; Siti Hadiaty Yuningsih; Nestia Lianingsih (International Journal of Ethno-Sciences and Education Research, 2026)
Mathematical literacy is one of the essential competencies that needs to be developed in school mathematics learning, as it plays an important role in equipping students to understand, interpret, and use mathematical concepts in various real-life situations. However, the development of mathematical literacy in learning practice still faces several challenges, such as the dominance of procedure-oriented instruction, the limited connection between mathematical content and everyday life contexts, and the lack of instructional strategies that promote students’ reasoning, problem-solving, and critical thinking. This article aims to examine the importance of mathematical literacy in school mathematics learning, identify the challenges encountered in its development, and describe various strategies that can be applied to support the improvement of students’ mathematical literacy. This article employs a literature review approach by examining various relevant scholarly sources related to mathematical literacy, mathematics learning, and instructional strategies. The results of the review indicate that the development of mathematical literacy can be supported through the implementation of contextual learning, problem-based learning, the use of non-routine problems, the strengthening of mathematical representation skills, and the integration of activities that encourage students’ mathematical reasoning and communication. Therefore, mathematical literacy needs to be positioned as a primary orientation in mathematics learning so that students are not only able to solve problems procedurally, but also able to use mathematics meaningfully in everyday life.